Evaluation Essentials: From A to Z (2nd ed.) - Mark Edward Verburg (Journal of MultiDisciplinary Evaluation)
A review of the book Evaluation Essentials: From A to Z (2nd ed.) by Marvin C. Alkin and Anne T. Vo, published in 2018 by Guilford Press.